The Comparison of Precision and Sensitivity in Contact Angle Measurement between Image Processing and Travelling Microscope Method on Composite Resin Material - Kurniatie, Menik Dwi; Sunarintyas, Siti; Herliansyah, Muhammad Kusumawan (2014)
Contact angle is the parameter to predict the material surface properties of composite resins as dental restorative materials. The latest development of contact angle measurements is the CAG (contact angle goniometry), which has several problems in reguler contact angle measurement. The limitation of equipment and relatively high cost cause developing a method that is more simple without reducing the level of accuracy of measurement. Contact angle measurements with a travelling microscope method provides quantitative data with some limitations, especially the conversion of analog to digital data is difficult to prevent human error. The development of quantification contact angle measurement with image processing method becomes a problem solver of manually data reading. This research conducted to compare of precision level and sensitivity of contact angle measurement between travelling microscope method and image processing method.